Posterior transverse interarch discrepancy on HbE β thalassemia patients - Yuniar Zen; Loes D. Sjahruddin (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: One of the symptoms that often arises on thalassemia patients is disharmony dentofacial, class II skeletal malocclusion, as a result of the malrelation of maxilla and mandible. This malrelation can be affected by either maxillary bone position, dentoalveolar maxillary position, mandibular bone position, dentoalveolar mandibular position, or combinations of those components. Purpose: The study was aimed to examine whether there is posterior transverse interarch discrepancy on the HbE β thalassemia patients or not. Methods: This study is an observational research with cross-sectional design. The sample consisted of 33 HbE β thalassemia patients and 33 non-thalassemia patients as a control group aged 12–14 years. Lateral cephalogram was carried out and dental casts of maxillary and mandibular dental arches were also taken in all of those patients. Results: There was no difference between the maxillary intermolar width of the HbE β thalassemia patients and that of the normal ones, but the mandibular intermolar width of the HbE β thalassemia patients was significantly smaller than that of the normal ones. Beside that, posterior transverse interarch discrepancy of of the HbE β thalassemia patients was significantly greater than that of the normal ones, which showed great difference between maxillary and mandibular intermolar widths. Conclusion: Posterior transverse interarch discrepancy of the HbE β thalassemia patients was different from that of the normal ones. The dentofacial abnormalities on the HbE β thalassemia patients aged 12–14 years primarily was due to disporposional dentofacial growth in the vertical, sagittal, and transversal directions, especially in the posterior region.Latar belakang: Salah satu akibat yang sering timbul pada penderita talasemia adalah disharmoni dentofasial berupa maloklusi skeletal kelas II yang merupakan kelainan hubungan maksila dan mandibula. Malrelasi ini dapat dipengaruhi oleh posisi maksila, posisi dentoalveolar maksila, posisi mandibula, dan posisi dentoalveolar mandibula atau kombinasi komponen ini dalam banyak variasi. Tujuan: Penelitian ini adalah untuk melihat apakah ada diskrepansi antar rahang arah tranversal di regio posterior pada penderita talasemia beta HbE. Metode: Penelitian ini adalah penelitian observasional dengan disain potong lintang. Sampel terdiri atas 33 penderita talasemia beta HbE dan 33 subjek normal (non talasemia) usia 12–14 tahun. Dilakukan pengambilan foto sefalogram lateral dan pembuatan model studi gigi RA dan RB pada semua subjek penelitian. Hasil: Jarak intermolar maksila tidak berbeda dengan subjek normal, namun jarak intermolar mandibula lebih kecil secara bermakna dibandingkan dengan subjek normal. Selain itu, diskrepansi antar rahang dalam arah transversal di regio posterior lebih besar secara bermakna dibanding subjek normal, yang menunjukkan besarnya selisih jarak antara jarak intermolar maksila dan jarak intermolar mandibula. Kesimpulan: Diskrepansi antar rahang arah transversal di regio posterior antara penderita talasemia beta HbE dengan subjek normal usia 12–14 tahun. Kelainan dentofasial pada penderita talasemia beta HbE usia 12–14 tahun disebabkan oleh pertumbuhan disporposional dentofasial berbeda arah vertikal, sagital dan transversal terutama di regio posterior.